Varying photosynthetic quotients strongly influence net kelp primary production and seasonal differences increase under warming - Franke, Kiara; Kroth, Frederike; Karsten, Ulf; Bartsch, Inka; Iñiguez, Concepción; Graiff, Angelika (Frontiers in Marine Science, 2024)
Reliable net primary production (NPP) estimations of kelp forests are important to evaluate their C-fixation potential. Oxygen evolution can be converted to C-fixation using photosynthetic quotients (PQs). Although high variability in PQs is known, the consequences for NPP are understudied in kelp species. The present study aimed (i) to quantify the variability of PQs, (ii) to model NPP and (iii) to assess the impact of warming on both. The kelp, Laminaria hyperborea, was studied near the island of Helgoland (North Sea, Germany) along a depth gradient (2, 4, 6 m below mean low water spring tide) across all four seasons. Blade discs were cultivated during at least 6 days per season under simulated ambient photon flux density (PFD) and temperature conditions and, in parallel, in a warming scenario (+ 4°C). PQs were calculated from parallel oxygen production and 14C-fixation measurements at saturating PFD at the end of the incubation period. Seasonal PQs varied between 1.7 and 4.4, with highest values in summer due to increased oxygen production. The warming scenario stimulated C-fixation in most seasons, lowering the PQ in comparison to ambient temperature conditions, while collection depth had no significant effect on PQs. The seasonal PQs were used to model daily NPP rates for kelp standing stock at 4 m depth. These daily NPP rates were compared between temperature treatments and with daily NPP rates based on fixed PQs. The warming scenario had a stimulating effect on daily NPP rates in the high-light season spring. In the low-light season autumn, warming resulted in negative daily NPP rates, as the high respiration rates could not be compensated by gross photosynthesis. Overall, annual NPP rate under warming conditions (347 g C m–2 yr–1) was 14% higher than the annual NPP rate under ambient conditions (303 g C m–2 yr–1). Modelling daily NPP with fixed PQs, which neglects the seasonal variation of the PQs, led to a high overestimation of up to 255%. We, therefore, recommend modelling NPP rates not with a fixed PQ, but with seasonal PQs determined under different temperature scenarios in order to obtain reliable future predictions.